Efeito do silicato tricálcico no capeamento pulpar direto: estudo experimental em ratos - Chicarelli, Lucio Paulo de Godoy (2016)
The direct pulp capping aims to protect the pulp by a bioactive material, allowing the maintenance of pulp vitality and the formation of mineralized barrier. The objective of this study was histologically comparing the pulp response of different materials, for continuity and morphology of the mineralized structure. It was 108 (one hundred and eight) teeth of 54 (fifty-four) male Wistar rats, eight (8) weeks old. Circular cavities were prepared in mesio-occlusal surface of the upper first molars and capped in accordance with the Group, which included the animal: group 1 with calcium hydroxide (CH); Group 2: MTA and group 3: Biodentine®. All cavities were sealed with cement resin modified glass ionomer cement (3M Vitremer -ESPE) and the animals euthanized at predetermined periods of seven (7), fourteen (14) and 21 (twenty one) days. The jaws were removed and fixed slides prepared and stained with HE (hematoxylin and eosin) for descriptive histological evaluation of inflammation and the formation of mineralized barrier. The results showed that the MTA and the Biodentine® exhibit less intense inflammatory reactions when compared to the CH, and the statistical comparison (Kruskal-Wallis) of formation and quality of the formed dentin barrier statistically different at 21 days between the CH groups for MTA and Biodentine, which were similar to each other. It can be concluded that the MTA and Biodentine® induce mineralized architecture of a more continuous and uniform barrier and less intense when compared to pulp response to CH.